Upaya Kepala Sekolah Dalam Meningkatkan Kepuasan Pelanggan Melalui Customer Intamacy - Siti Halimatus Syakdiyah (CV Edujavare Publishing, 2023)
This study aims to analyze and understand how to plan and implement the principal's efforts to increase customer satisfaction through customer engagement , by focusing on the principal's efforts to increase customer satisfaction through unusual customer engagement . This study uses a qualitative case study type approach, in which the researcher tries to understand the phenomena that occur in the institution, through interviews, observation and documentation. The results of the study show that planning and implementation in increasing customer satisfaction through customer engagement is first own participant educate have morals karimah And worship with right ,. second own participant students who achieve optimally, third school give innovation so no stagnant And boring , fourth exists services performed with full heart fifth management and activity Study teach or teaching and learning services , sixth service means infrastructure , seventh development character participant educate with give example And require 3 S smile , greet , polite